Associations between anthropometric indicators and refraction in school-age children during the post-COVID-19 era - Du, Wenzheng; Ding, Gang; Guo, Xiying; Abudukeyimu, Kadiya; Wang, Yanzhu; Wang, Lijun; Qi, Xiaoli; Ning, Yuxian; Hua, Ning; Song, Linlin; Li, Xue; Li, Jing; et al. (Frontiers in Public Health, 2023)
Purpose To explore the associations between anthropometric indicators and refraction in school-aged children in the post-COVID-19 era. Methods Data were collected from 25,644 children aged 7 to 12 years in 48 elementary schools in Tianjin. The comprehensive examination included height, weight, systolic blood pressure (SBP), diastolic blood pressure (DBP), refraction, and calculation of BMI, with a follow-up visit after 6 months. Myopia was defined as spherical equivalent refraction (SER) ≤-0.50 diopter (D). Bivariate correlation coefficients and multiple linear regression models were used to explore the cross-sectional and longitudinal associations between anthropometric indicators (height, weight, BMI, SBP, and DBP) and refraction. Results The mean changes in height, weight, BMI, SBP, DBP, and SER of the participants were 4.03 ± 2.18 cm, 3.10 ± 2.39 kg, 0.45 ± 1.16 kg/m2, 2.26 ± 14.74 mmHg, 2.18 ± 11.79 mmHg and −0.17 ± 0.51 D, respectively. Overall, height, weight, BMI, SBP, and DBP were all correlated with SER (r = −0.324, r = −0.234, r = −0.121, r = −0.112, r = −0.066, both p < 0.001), and changes in height and weight were correlated with changes in SER (r = −0.034, −0.031, both p < 0.001). Furthermore, multiple linear regression analysis revealed that the association of BMI, SBP, and DBP with SER was significant in myopic children but not in non-myopic children. The association between changes in weight and changes in SER was only present in non-myopic children but not in myopic children. Conclusion Height and weight were negatively correlated with SER in both cross-sectional analysis and longitudinal changes, indicating that children's height, weight and growth rate may be used as a reference indicator for myopia risk prediction and myopia progression monitoring.